p16INK4A immunohistochemical overexpression in premalignant and malignant oral lesions infected with human papillomavirus - Fregonesi, Paula Andrea Gabrielli [UNESP]; Teresa, Debora Barreto [UNESP]; Duarte, Roberta Aparecida [UNESP]; Benatti Neto, Carlos[UNESP]; Oliveira, Maria Rita Brancini de [UNESP]; Soares, Christiane Pienna [UNESP] (SAGE Publications, 2003)
Human papillomavirus (HPV) is believed to promote the oncogenic process, and the correlation between viral oncoproteins and dysfunction of p16 INK4A tumor suppressor protein in oral lesions is controversial. To test the hypothesis that anogenital HPV types participate in disruption of the regulation of p16INK4A suppressor protein in oral lesions, we analyzed 46 oral biopsy specimens for the presence of HPV 6/11 and 16/18 by in situ hybridization (ISH) and for p16INK4A expression by immunohistochemistry (IHC). Eighteen (39%) of the 46 oral lesions were HPV-positive and 28 (61%) were HPV-negative. HPV 6/11 DNA was found in 5 (11%) and HPV 16/18 in 13 (28%) of 46 biopsies. Nine of the 18 HPV-positive oral lesions (50%), assessed by catalyzed signal amplification coupled to ISH (CSA-ISH), gave high-intensity p16INK4A immunostaining. Focal and diffuse patterns were observed in 11/13 (77%) lesions with HPV 16/18, focal immunopositivity in 3/5 (80%) with HPV 6/11, and negative or sporadic p16-labeling in 18/28 (64%) without the presence of HPV DNA. These results showed a strong association between overexpression of p16 protein and malignant oral lesions, mainly those infected by HPV 16/18. We can conclude that high-risk HPV types are associated with p16 overexpression, and p16 may serve as a biomarker in oral cancer related to high-risk HPV infection.
Keywords: HPV; Immunohistochemistry; In situ hybridization; Oral cancer; p16INK4A; oncoprotein; protein p16; virus DNA; benign tumor; carcinogenicity; clinical article; human; human tissue; immunohistochemistry; in situ hybridization; malignant neoplastic disease; mouth cancer; mouth lesion; oral biopsy; precancer; priority journal; protein expression; virus infection; Wart virus; Biopsy; Cyclin-Dependent Kinase Inhibitor p16; DNA Probes; DNA, Viral; Humans; In Situ Hybridization; Mouth Neoplasms; Papillomaviridae; Papillomavirus Infections; Precancerous Conditions; Risk Factors; Tumor Markers, Biological; Tumor Virus Infections; DNA viruses; Human papillomavirus; Human papillomavirus type 16; Human papillomavirus types; Papillomavirus